GAMBARAN PERILAKU BUANG AIR BESAR SEMBARANG PADA MASYARAKAT DI RW 13 RT 5 PERUMNAS II WAENA KOTA JAYAPURA - Makualaina, Fenska Narly (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2024)
Background: Semarang defecation behavior continues to persist globally, including in Indonesia and in the city of Jayapura. One of the causes is the lack of safe, comfortable and healthy public sanitation facilities as well as hereditary habits. This will have an impact on people's health so there is a need for public awareness regarding correct defecation behavior. Objective: To determine the description of open defecation behavior in the community in RW 13 RT 5 Perumnas II Waena, Jayapura City. Research method: Quantitative descriptive research type. with a total sample of 71 heads of families or representatives using purposive sampling, data collection using a questionnaire and analyzed univariately. Result: Open defecation behavior in RW 13 RT 5 Perumnas II Waena, Jayapura City was mostly in the positive category, as many as 43 people (60.6%) compared to negative behavior as many as 28 people (39.4%). Cnclussion: The majority of public defecation behavior is carried out positively, so it needs to be further improved so that awareness of negative behavior will arise among the public by providing clean, healthy and comfortable latrine facilities supported by health promotion efforts from local agencies.